The gift of the algorithm: beyond autonomy and control - Chamberlain, Alan; De Roure, David (Performed at Audio Mostly 2017: Augmented and Participatory Sound/Music Experiences, 23-26 August. Queen Mary University of London (London, UK), 2017)
This piece brings together, participation, algorithmic composition and augmentation (as a mechanism by which people can work together to augment and support a composer’s workflow). The performance is about understanding the ways in which composition and performance can be understood, socially, aesthetically and scientifically. This performance becomes a piece of research and design in its own right, a more experimental manifestation of HCI, but it also demonstrates and disrupts conventional production and performance by making the multiple layers of practice and provenance obvious. *See Program notes for a fuller description of the piece for public consumption. We also aim to discuss this further and demo at the Performance workshop that we have submitted.